2012
DOI: 10.4236/acs.2012.24038
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Optical Properties at Four Sites in Thailand

Abstract: This paper presents column integrated aerosol optical properties including aerosol optical depth (AOD), Angstrom wavelength exponent (), single scattering albedo (SSA), and size distribution from ground-based measurements at four sites in Thailand: Chiang Mai (18.78˚N, 98.98˚E), Ubon Ratchathani (15.25˚N, 104.87˚E), Nakhon Pathom (13.82˚N, 100.04˚E), and Songkhla (7.2˚N, 100.60˚E). Results show a marked seasonal trend in AOD at 500 nm for the first three stations, with the monthly average maxima of 0.92, 0.78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…The later reason can also explain the overestimations of the OMI UV index under clear sky conditions. The highest bias is found at Chiang Mai which is an urban area, while the lowest bias occurs at Songkhla, the coastal area with low aerosol loading (Janjai et al ., ). It is also noticed that the RMSE for the case of all sky conditions is higher than that of clear sky conditions.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The later reason can also explain the overestimations of the OMI UV index under clear sky conditions. The highest bias is found at Chiang Mai which is an urban area, while the lowest bias occurs at Songkhla, the coastal area with low aerosol loading (Janjai et al ., ). It is also noticed that the RMSE for the case of all sky conditions is higher than that of clear sky conditions.…”
Section: Resultsmentioning
confidence: 97%
“…The result also indicates that the difference between the ground‐based and satellite‐estimated values for Songkhla is less than that for the other sites. This is maybe because of the fact that Songkhla has less aerosol loading, as compared to the other sites (Janjai et al ., ). Table shows the confidence interval of the measurement and the satellite datasets for the case of all sky conditions.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Both sites primarily sample nearby agricultural burning, and forest burning from elsewhere in the region. In contrast, the site in the city of Chiang Mai (north-western Thailand) was not used as, while close to biomass burning source regions, it also has a significant urban contribution to the aerosol, coupled with the local topography leading to a "trapping" of pollutants (Janjai et al, 2012;Gautam et al, 2013). An exception is central and eastern Russia, where two sites (Tomsk 22 and Yakutsk) were included because the sites individually have a comparatively low data volume.…”
Section: Site Selectionmentioning
confidence: 99%
“…Both sites primarily sample nearby agricultural burning, and forest burning from elsewhere in the region. In contrast, the site in the city of Chiang Mai (north-western Thailand) was not used as, while close to biomass burning source regions, it also has a significant urban contribution to the aerosol, coupled with the local topography leading to a "trapping" of pollutants (Gautam et al, 2012;Janjai et al, 2012). Another point to note is the omission of sites from the Sahel; although AERONET contains several long-term sites in this region, the dry season biomass burning peak here (November-February) due to burning of grassland, cropland, and shrubs coincides with strong dust activity, such that the aerosol is normally a mixture of biomass burning smoke and dust (Pandithurai et al, 2001;Roberts et al, 2009 Johnson et al (2008) and Eck et al (2010) found cases where these smoke aerosols were highly absorbing, with midvisible SSA as low as 0.76, although the more common cases of mixed smoke and dust in this region are less absorbing.…”
Section: Data Selectionmentioning
confidence: 99%